Ethylene Improves Root System Development under Cadmium Stress by Modulating Superoxide Anion Concentration in Arabidopsis thaliana - Abozeid, Ann; Ying, Zuojia; Lin, Yingchao; Liu, Jia; Zhang, Zhonghua; Tang, Zhonghua (Frontiers in Plant Science, 2017)
This work aims at identifying the effects of ethylene on the response of Arabidopsis thaliana root system to cadmium chloride (CdCl2) stress. Two ethylene-insensitive mutants, ein2-5 and ein3-1eil1-1, were subjected to (25, 50, 75, 100 μM ) CdCl2 concentrations, from which 75 μM concentration decreased root growth by 40% compared with wild type Col-0 as a control. Ethylene biosynthesis increased in response to CdCl2 treatment. The length of primary root and root tip in ein2-5 and ein3-1eil1-1 decreased compared with wild type after CdCl2 treatment, suggesting that ethylene play a role in root system response to Cd stress. The superoxide concentration in roots of ein2-5 and ein3-1eil1-1 was greater than in wild type seedlings under Cd stress. Application of exogenous 1-aminocyclopropane-1-carboxylic acid (ACC) (a precursor of ethylene biosynthesis) in different concentrations (0.01, 0.05 and 0.5 μM) decreased superoxide accumulation in Col-0 root tips and increased the activities of superoxide dismutase (SOD) isoenzymes under Cd stress. This result was reversed with 5 μM AIB (an inhibitor of ethylene biosynthesis). Moreover, it was accompanied by increase in lateral roots number and root hairs length, indicating the essential role of ethylene in modulating root system development by controlling superoxide accumulation through SOD isoenzymes activities. The suppressed Cd-induced superoxide accumulation in wild type plants decreased the occurrence of cells death while PCD was initiated in the root tip zone, altering root morphogenesis (decreased primary root length, more lateral roots and root hairs) to minimize the damage caused by Cd stress, whereas this response was absent in the ein2-5 and ein3-1eil1-1 seedlings. Hence, ethylene has a role in modulating root morphogenesis during CdCl2 stress in A. thaliana by increasing the activity of SOD isoenzymes to control superoxide accumulation.